1971
DOI: 10.1139/v71-490
|View full text |Cite
|
Sign up to set email alerts
|

The Vibrational Spectra of Silane and Germane Derivatives. Part IV. The Infrared and Raman Spectra of the Iodo(methyl)germanes

Abstract: The infrared and Raman spectra of the series of iodo(methyl)germanes, CH3GeI3, (CH3)2GeI2, and (CH3)3GeI have been recorded. A normal coordinate analysis based on a modified valence force field confirms the a priori assignments for all of the fundamental frequencies except the torsional modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…This band appears by FSD at 843 cm -1 , in agreement with the observation from the LT spectra (Figure ). Previously, only one band was observed in this region, at 840 cm -1 in the infrared spectrum of the liquid, which was also assigned to the ν 19 rocking mode . The feature at 763 cm -1 in both the RTIR and LTIR spectra is due to the ν 20 rocking mode, which appears in the Raman spectrum (760 cm -1 ) as a very weak depolarized band.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…This band appears by FSD at 843 cm -1 , in agreement with the observation from the LT spectra (Figure ). Previously, only one band was observed in this region, at 840 cm -1 in the infrared spectrum of the liquid, which was also assigned to the ν 19 rocking mode . The feature at 763 cm -1 in both the RTIR and LTIR spectra is due to the ν 20 rocking mode, which appears in the Raman spectrum (760 cm -1 ) as a very weak depolarized band.…”
Section: Resultsmentioning
confidence: 85%
“… a Units are mdyn Å -1 for stretching and stretching/stretching interactions and mdyn Å rad -2 for deformations and deformation/deformation interactions. b Calculated with the SVFF method, taken from ref . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the spectroscopic data of the three compounds (CH3) 2-GeX[S2CN(CHa)2], X= Cl, Br, I (Chadha, Drake & Sarkar, 1986), indicated that similar distorted trigonal bipyramidal structures might be expected for the bromo and iodo derivatives. In particular, the values of the Ge-Br and Ge-I stretching vibrations were of the order of 80 and 100 cm -1 respectively lower than in the related four-coordinate germanium halide derivatives (CH3)2GeBr 2 and (CH3)2GeI 2 (Anderson, Barker, Drake & Hemmings, 1971;Griffiths, 1964;Van de Vondel, Van der Kelen & Van Hooydonk, 1970). We have completed the crystal structures of bromo(N,Ndimethyldithiocarbamato)dimethylgermanium, (CH3) 2-GeBr[SECN(CHa)2], and (N,N-dimethyldithiocarbamato)iododimethylgermanium, (CH3)EGeI[S2CN-(CH3)2] , which not only confirm the predictions based on spectroscopy but also draw attention to some interesting trends.…”
Section: Introductionmentioning
confidence: 95%
“…The use of complex aluminates as synthetic reagents has been studied considerably (8,19). In this study, these were extended to Li[Al(SCH,),] to include a convenient preparation of a series of methylthiosilanes by the general reaction:…”
Section: Resultsmentioning
confidence: 99%